Performance Evaluation of TabPFN for Student Depression Prediction Across Varying Sample Sizes - Florentina Yuni Arini; Muhammad Kahvi Khakam Syah; Fernando Dinar Setiawan; Rafif Musyaffa Indarto; Muhammad Danil Aminuddin; Fairuz Trideas Hilmy; Ahmad Imam Mutaqin (Faculty of Computer Science - Universitas Indonesia, 2026)
Early prediction of depression in students is a critical challenge, often hindered by the scarcity of large, labelled datasets. While supervised tabular classifiers such as Random Forest, XGBoost, and CatBoost are powerful, they typically require sufficient data and careful hyperparameter optimisation (HPO) to generalise effectively. This paper evaluates the Tabular Prior-data Fitted Network (TabPFN), a foundation model for supervised tabular learning, as a zero-shot classifier for student depression prediction. We conduct a comparative study against five robustly configured baseline classifiers (Random Forest, XGBoost, CatBoost, SVM, and Naive Bayes) across three publicly available student mental health datasets of varying sizes sourced from Kaggle: a micro-sample dataset with 101 instances, a small-sample dataset with 7,022 instances, and a moderate-sample dataset with 27,901 instances. Dataset categorization by size is defined relative to TabPFN v2.5's operational capacity of 50,000 samples rather than general machine learning conventions. Using F1-Score as the primary evaluation metric, our empirical results demonstrate a performance crossover linked to data size. On the microsample, imbalanced dataset, TabPFN achieved the highest F1-Score of 0.727, outperforming the best baseline (CatBoost and Random Forest, F1 = 0.667). In the ablation study, both raw and preprocessed inputs yielded identical results for TabPFN on this dataset, highlighting its capacity to handle unprocessed data without performance loss. On the small and moderate datasets, the tuned baselines were competitive or superior, with CatBoost leading on the moderate-sample dataset (F1 = 0.869). We conclude that TabPFN is an effective and efficient baseline for depression prediction tasks in datascarce environments, providing competitive results without HPO, while traditional ensembles remain preferred for larger datasets.